2014 International Conference on Simulation of Semiconductor Processes and Devices (SISPAD) 2014
DOI: 10.1109/sispad.2014.6931563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon-related oxide defects on the reliability of 4H-SiC MOSFETs

Abstract: In this work, we use density functional theorybased calculations to study the hole trapping properties of single carbon-related defects in silicon dioxide. We show that such interstitials are stable in the carboxyl configuration, where the interstitial carbon atom remains three-fold coordinated with chemical bonds to two Si atoms and an oxygen atom (Si-[C=O]-Si). Using formation energy calculations, we observed a +2 to neutral charge transition level for carboxyl defect within the 4H-SiC bandgap. This leads us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This phenomenon is well understood on silicon devices and improved oxidation, surface treatment and anneal processes have reduced the occurrence. However, in SiC power MOSFETs, as a result of the presence of carbon atoms during the oxidation of the semiconductor [17][18][19], the increased oxide, interface and near-interface traps make NBTI and PBTI more active. The threshold voltage shift recovers when the gate bias is removed, and this recovery is accelerated if the gate is biased with the opposed polarity to the stress [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is well understood on silicon devices and improved oxidation, surface treatment and anneal processes have reduced the occurrence. However, in SiC power MOSFETs, as a result of the presence of carbon atoms during the oxidation of the semiconductor [17][18][19], the increased oxide, interface and near-interface traps make NBTI and PBTI more active. The threshold voltage shift recovers when the gate bias is removed, and this recovery is accelerated if the gate is biased with the opposed polarity to the stress [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, in SiC power MOSFETs, as a result of the presence of carbon atoms during the oxidation of the semiconductor [17][18][19], the increased oxide, interface and near-interface traps make NBTI and PBTI more active. The threshold voltage shift recovers when the gate bias is removed, and this recovery is accelerated if the gate is biased with the opposed polarity to the stress [19]. A thorough comparison of different power devices under accelerated gate bias stress tests was presented in [20], where it was shown that the voltages required to damage the gate oxide are considerably higher for Si devices.…”
Section: Introductionmentioning
confidence: 99%
“…Bias Temperature Instability (BTI) is a well-known problem in insulated gate power devices. It is a more critical problem in SiC due to the reduced band offsets between the gate oxide and the wide bandgap semiconductor [1][2][3], as well as the increased interface trap density [4][5][6] resulting from the presence of carbon during the oxidation. Positive charge trapping from negative gate bias stress causes a downward shift in the threshold voltage (VTH) referred to as Negative Bias Temperature Instability (NBTI).…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of the gate oxide of SiC MOSFETs have been the subject of different studies in the recent years [1][2][3][4]. The main challenge of SiC MOSFETs is the existence of carbon [5,6], resulting in an increased trap density in the oxide and at the interface. This makes the SiC/SiO2 interface of SiC MOSFETs more complex than the Si/SiO2 interface in Si MOSFETs and IGBTs.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in equations 3and 4, VGG is directly proportional to the turn-ON voltage and current switching rates (dVDS/dt and dIDS/dt). At turn-OFF, as the gate drive voltage is 0 V, VGP is the critical factor since VGG does not appear in equations (5) and (6).From the results shown in Fig. 4 and the analytical equations, it is clearly observed that the penalization because of the reduction of the gate driver voltage will be in the turn-ON switching energy, as the turn-OFF switching energy will be gate driver voltage independent.…”
mentioning
confidence: 95%